Hydride-Induced Reconstruction of Pd Electrode Surfaces: A Combined Computational and Experimental Study - Ngoipala, Apinya; Schott, Christian; Briega-Martos, Valentin; Qamar, Minaam; Mrovec, Matous; Javan Nikkhah, Sousa; Schmidt, Thorsten O.; Deville, Lewin; Capogrosso, Andrea; Moumaneix, Lilian; Kallio, Tanja; Viola, Arnaud; et al. (Advanced Materials, 2025)
Designing electrocatalysts with optimal activity and selectivity relies on a thorough understanding of the surface structure under reaction conditions. In this study, experimental and computational approaches are combined to elucidate reconstruction processes on low-index Pd surfaces during H-insertion following proton electroreduction. While electrochemical scanning tunneling microscopy clearly reveals pronounced surface roughening and morphological changes on Pd(111), Pd(110), and Pd(100) surfaces during cyclic voltammetry, a complementary analysis using inductively coupled plasma mass spectrometry excludes Pd dissolution as the primary cause of the observed restructuring. Large-scale molecular dynamics simulations further show that these surface alterations are related to the creation and propagation of structural defects as well as phase transformations that take place during hydride formation.
CRIS-Team Scopus Importer:2025-02-04
Keywords: electrochemical scanning tunneling microscopy; molecular dynamics simulations with machine learning potential; online inductively coupled plasma mass spectrometry; palladium hydride formation; proton electroreduction; strain relaxation; surface reconstruction